The Effect of Android-Based Learning and Learning Motivation on Learning Outcomes in Computer Science in the 10th Grade at SMK Negeri 1 Sumatera Barat - Novita Sari; Rizky Ema Wulansari; Syahril; Ika Parma Dewi; Abdul Habib Arrasyidi Desky; Liza Mahera (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effects of Android-based learning and learning motivation on the Informatics learning outcomes of tenth-grade students at SMK Negeri 1 Sumatera Barat. Android-based learning is increasingly important in vocational education because it supports the development of digital competencies and independent learning skills required in the digital era. Previous studies have generally examined Android-based learning and learning motivation separately, while evidence regarding their interaction remains limited. This study employed a quasi-experimental method with a 2 × 3 factorial design involving 84 students in experimental and control classes. Data were collected using a learning motivation questionnaire and a learning outcomes test and analyzed through descriptive statistics and Two-Way ANOVA. The results showed that the experimental class achieved a higher mean posttest score (78.61) than the control class (68.33). The N-Gain score was also higher in the experimental class (0.55) than in the control class (0.34). Two-Way ANOVA revealed significant effects of the learning model (F = 32.47, p < 0.05), learning motivation (F = 22.86, p < 0.05), and their interaction (F = 6.43, p < 0.05) on learning outcomes. These findings indicate that Android-based learning is more effective when supported by high student motivation. This study provides empirical evidence for integrating technology-enhanced learning and motivational factors in vocational Informatics education.